An overview of the place of games and gamification in SLA from the global skills perspective: A narrative literature review - Orak, Suheyla Demirkol (Nova Science Publishers Inc., 2025)
Gamification has emerged as a transformative approach in second language acquisition (SLA), leveraging technology to create engaging and student-centered learning environments. This systematic literature review examines the role of gamification in enhancing linguistic competence and fostering self-efficacy among learners. Research highlights the motivational factors of gaming, including curiosity, challenge, social interaction, and escapism, which contribute to learners' enjoyment and cognitive engagement. By incorporating gamified strategies, students benefit from opportunities to develop higher-order thinking skills, creativity, and 21st-century competencies. Findings reveal that technology-integrated gamification facilitates independent learning, enabling students to access diverse resources such as online courses, e-books, and interactive programs. This shift from teacher-centered to student-centered methodologies empowers learners to collaborate, improve their cognitive and verbal abilities, and connect new knowledge with prior learning. Moreover, gamification provides a supportive, competitive environment that enhances communication skills and self-efficacy, particularly for students with low language proficiency. While gamification is effective in SLA, its integration into course curricula remains underexplored. The review underscores the need for gamification to be recognized as a fundamental teaching approach for 21st-century learners immersed in digital and virtual landscapes. Teachers, curriculum developers, and syllabus designers are encouraged to create structured gamified materials that promote meaningful communication and motivation. By doing so, gamification can serve as a cornerstone in modern language education, addressing the evolving needs of digital-native learners. © 2025 Nova Science Publishers, Inc. All rights reserved.
Keywords: Games; Gamification; Gamification in ELT; GEN Z; Technology enhanced games